Anterior Urethral Strictures in Children: Disease Etiology and Comparative Effectiveness of Endoscopic Treatment vs. Open Surgical Reconstruction - Vetterlein, Malte W.; Weisbach, Lars; Riechardt, Silke; Fisch, Margit (Frontiers in Pediatrics, 2019)
Pediatric anterior urethral strictures are rare and recommendations regarding treatment strategies derive from small monocentric case series. In 2014, a collaborative effort of the Société Internationale d’Urologie and the International Consultation on Urological Diseases drafted the first systematic and evidence-based guideline for diagnosis and treatment of urethral strictures in children. Against this backdrop, we performed an updated literature review to provide a comprehensive summary of the available evidence and contemporary outcomes with a focus on comparative effectiveness of endoscopic treatment (dilation or urethrotomy) versus open surgical reconstruction. Overall, 22 articles reporting on children with anterior urethral strictures were included into the review. Most strictures were iatrogenic (48%) and traumatic (34%), whereas congenital (13%), inflammatory (4%) or postinfectious strictures (1%) were rather rare. The cumulative success rate of endoscopic treatment and urethroplasty was 46% (range: 21-75; N=334) and 84% (range: 25-100; N=347), respectively. After stratifying patients according to urethroplasty technique, success rates were 82% (range: 25-100; N=206) for excision and primary anastomosis, 94% (range: 75-100; N=40) for graft augmentation, 97% (range: 87-100; N=30) for flap urethroplasty, and 70% (one study; N=20) for pull-through urethroplasty. In conclusion, endoscopic approaches are rather ineffective in the long-term and open surgical reconstruction via urethroplasty should be preferred to avoid multiple, repetitive interventions. Future research may involve multi-institutional, collaborative, and prospective studies, incorporating well-defined outcome criteria and assessing objective surgical endpoints as well as patient-reported functional outcomes.